Effect of Plyometric Training on Speed and Change of Direction Ability in Elite Field Hockey Players - Singh, Jasdev; Appleby, B.; Lavender, Andrew (2018)
This study investigated the effects of two plyometric training protocols on sprint and change of direction (COD) performance in elite hockey players. A parallel-group randomized controlled trial design was used and seventeen elite male and female field hockey players were randomly allocated into either low-to-high (L-H, n = 8) or high-to-low (H-L, n = 9) training groups. Each group performed separate variations of the drop jump exercise twice weekly for six weeks, with an emphasis on either jump height (L-H) or drop height (H-L). Performance variables assessed included sprint times over 10 m and 20 m, as well as 505 time. A two-way repeated measures analysis of variance was performed and Cohen's d effect sizes (ESs) were calculated. The H-L group displayed a significant small ES improvement from baseline to post-training in the 10 m sprint (1.893 ± 0.08 s pre vs. 1.851 ± 0.06 s post) (ES = -0.44) (p < 0.05). Differences between groups for 10 m and 20 m sprint performance failed to reach statistical significance, and no significant differences were observed within or between groups for 505 time. These findings highlight the difficulty in substantially enhancing speed and COD ability in highly trained athletic populations through the addition of a low volume, short duration plyometric training protocol.